Effects of leaf response velocity on spray deposition with an air-assisted orchard sprayer - Li, Jun; Li, Zhiqiang; Ma, Yakun; Cui, Huajun; Yang, Zhou; Lu, Huazhong (International Journal of Agricultural and Biological Engineering, 2021)
The interaction between leaves and airflow has a direct effect on the droplet deposition characteristics of the leaf canopy. In order to make clear the mechanism of droplet deposition in terms of the interaction between the droplets and leaves from the point of the leaf aerodynamic response velocity, the leaf movement under different airflow velocities and the influence of the leaf aerodynamic response on droplet coverage ratio were investigated. The effect of the aerodynamic response velocity of a leaf on the droplet deposition of the leaf surface was investigated. The aerodynamic characteristics of the leaf were analyzed theoretically. Boundary layer theory from fluid mechanics was used to develop a model of the leaf aerodynamic response velocity to nonperiodic excitations based on a convolution integral method. Target leaf aerodynamic velocities were detected using a high-speed camera, and the results indicated that the modeled leaf aerodynamic response velocity matched the measured values. At given conditions of spray liquid and leaf surface texture, the spray test showed that the droplet coverage ratio was influenced by the leaf aerodynamic response velocity, the droplet coverage ratio increased and then decreased with the leaf response velocity. Through analyze four droplets deposition state, the highest droplet deposition ratio and best deposition state on the leaf surface occur when the leaf aerodynamic response velocity was less than 0.14 m/s. According to the analysis of droplet deposition states, the uniformity of the droplet size and quantity distribution of droplets on the leaf surface related to the leaf aerodynamic response velocity. The results can provide a basis for the design and optimization of orchard air sprayers. Keywords: air-assisted spray, leaf wind vibration, leaf aerodynamic response velocity, droplet deposition states, droplet retention, orchard DOI: 10.25165/j.ijabe.20211401.5435 Citation: Li J, Li Z Q, Ma Y K, Cui H J, Yang Z, Lu H Z. Effects of leaf response velocity on spray deposition with an air-assisted orchard sprayer. Int J Agric & Biol Eng, 2021; 14(1): 123–132.